Identification of SARS‐CoV‐2 RNA in healthcare heating, ventilation, and air conditioning units. (29th June 2021) - Horve, Patrick F.; Dietz, Leslie G.; Fretz, Mark; Constant, David A.; Wilkes, Andrew; Townes, John M.; Martindale, Robert G.; Messer, William B.; Van Den Wymelenberg, Kevin G.
Abstract: Evidence continues to grow supporting the aerosol transmission of severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2). To assess the potential role of heating, ventilation, and air conditioning (HVAC) systems in airborne viral transmission, this study sought to determine the viral presence, if any, on air handling units in a healthcare setting where coronavirus disease 2019 (COVID‐19) patients were being treated. The presence of SARS‐CoV‐2 RNA was detected in approximately 25% of samples taken from ten different locations in multiple air handlers. While samples were not evaluated for viral infectivity, the presence of viral RNA in air handlers raises the possibility that viral particles can enter and travel within the air handling system of a hospital, from room return air through high‐efficiency MERV‐15 filters and into supply air ducts. Although no known transmission events were determined to be associated with these specimens, the findings suggest the potential for HVAC systems to facilitate transfer of virions to locations remote from areas where infected persons reside. These results are important within and outside of healthcare settings and may present necessary guidance for building operators of facilities that are not equipped with high‐efficiency filtration. Furthermore, the identification of SARS‐CoV‐2 in HVAC components indicates the potential utility as an indoor environmental surveillance location.